Proliferative Role of Kv11 Channels in Murine Arteries - Barrese, Vincenzo; Cidad, Pilar; Yeung, Shuk Y.; López-López, Jose R.; McNeish, Alister J.; Ohya, Susumu; Pérez-García, Maria T.; Greenwood, Iain A. (Frontiers in Physiology, 2017)
K+ channels encoded by the ether-a-go-go related gene (ERG1 or KCNH2) are important determinants of the cardiac action potential. Expression of both cardiac isoforms (ERG1 and ERG1b) were identified in murine portal vein and distinctive voltage-gated K+ currents were recorded from single myocytes. The aim of the present study was to ascertain the expression and functional impact of ERG channels in murine arteries. Methods: Quantitative RT-PCR was undertaken on RNA extracted from a number of murine arteries. Immunofluorescence was performed on single vascular smooth muscle cells using antibodies against the ERG1 expression product (Kv11.1). Single cell electrophysiology was performed on myocytes from portal vein and several different arteries, complimented by isometric tension recordings. Proliferation assays were undertaken on smooth muscle cells isolated from femoral arteries. Results: ERG1 transcripts were detected in all murine blood vessels, and Kv11.1 immunofluorescence was observed in all smooth muscle cells. However, K+ currents with properties consistent with ERG channels were only recorded in portal vein myocytes. Moreover, ERG channel blockers (E4031 or dofetilide, 1µM) failed to depolarise carotid arteries or produce contraction. Proliferation of arterial smooth muscle cells was associated with a marked increase in ERG1 expression and ERG blockers suppressed proliferation significantly. Conclusions: These data reveal that arterial blood vessels express ERG channels that appear to be functional silent in contractile smooth muscle but contribute to proliferative response.